Learning spaces for health sciences – what is the role of e-learning in physiotherapy and occupational therapy education? A literature review. (2nd January 2018) - Unge, Jeannette; Lundh, Pernilla; Gummesson, Christina; Amnér, Gunilla
Abstract : Our aim was to explore the current state of e-learning activities during physiotherapy and occupational therapy education, in relation to theories and models about learning. What kind of e-learning activities were described and which were the intentions behind the use of digital support expressed in current physiotherapy and occupational therapy literature? The search was done using four different search engines. Twenty articles met the inclusion criteria and where included. Three categories of e-learning activities were identified. (1) Communication space, (2) enabling learning activities, and (3) ambition to create a learning space. The first category revolved around the individual use of social media, how it could be developed and the benefits from it in a learning environment. The second category had a narrow focus on a specific element of the learning sequence and how it is mastered and/or perceived. The third category, the theoretical base, is varied covering considerations about the learning itself from constructivist and connectivist origin and theories pertaining to the design of teaching and learning activities. The underlying theoretical support for the activity developed was only described in some of the studies. To furthering the field clearer rationale informed by research developed theories and models would promote system alignment and educational development. This review maybe of value to educators in physiotherapy and occupational therapy as it proposes frameworks that may guide in identifying approaches to improve education.